Predicting Performance and Roll-Rate Minimization of a High-Powered Model Rocket - Schilder, Nicole; Naumann, Patrick; Faber, Jordan (Proceedings of the Wisconsin Space Conference, 2023)
The Collegiate Rocket Launch is a competition sponsored by the Wisconsin Space Grant Consortium which challenges student teams from colleges throughout the state of Wisconsin to design, build, and launch a high-powered model rocket. Teams are scored based on quality of technical reports, project management, outreach, and the competition flight. The 2022 competition challenged teams to create an active control system that minimized the roll rate of the rocket while in flight, as well as reach but not exceed a target altitude of 3,500 feet. Marquette Rocketry is proud to have placed first in the competition and given the title mission grand champion.